Syntaxonomıcal contrıbutıon to the vegetatıon classıfıcatıon of Türkiye from SW Anatolıa: A plant dıversıty hotspot (Journal of Forestry, 2025)
This study was carried out to determine the vegetation diversity and gradient of the Bencik Mountain in SW Anatolia, Türkiye, which is a plant biodiversity hotspot. The field sampling was realized in accordance with the Braun-Blanquet’s methodology. For the classification of communities, hierarchical cluster analysis was used. Ecological interpretation of the defined communities was done by nonmetric multi-dimensional scaling with passive projection of topographical variables. Five plant communities belonging to different vegetation types (forest, macchia and regressive successional stage) were identified. Except for regressive successional stage, the others were described at the association level. Three of them were newly described. The pine-dominated forests are represented by Hymenocarpo circinnati-Pinetum brutiae under the alliance Styraco officinalis-Pinion brutiae (Pinetalia halepensis, Pinatea halepensis) and Vicio lathyroidis-Pinetum pallasianae under the alliance Adenocarpo-Pinion pallasianae (Erico-Pinetalia, Erico-Pinetea). Both of them are new associations. The riparian sites are represented by Nerio oleandri-Platanetum orientalis under the alliance Platanion orientalis (Populetalia albae, Alno glutinosae-Populetea albae). The macchia is represented by Daphno gnidiois-Quercetum cocciferae, a new association belonging to the alliance Quercion cocciferae (Quercetalia cocciferae, Quercetea ilicis). The regressive successional stage is represented by the Aegilops triuncialis-Clypeola jonthlaspi community, which resulted from the overgrazing and intensive human use of Quercus coccifera macchia. Floristic differentiation of the study area vegetation is significantly correlated with topographical variables (elevation and aspect). This study not only indicated the diverse vegetation richness of the area and its nature conservation value but also made an important contribution to the understanding of Mediterranean vegetation in Türkiye.